Obtaining and tuning of adsorption energies for reaction intermediates in oxygen electrocatalysis - Zhang, Junming (Nanyang Technological University, 2022)
Adsorption energy (AE) of reactive intermediates adsorbed on the surface of electrocatalysts is currently the most crucial descriptor for electrochemical reactions (e.g., water splitting, fuel cell, nitrogen fixation, and carbon dioxide reduction). It bridges the gap between structure and performance of the electrocatalyst through several recognized relations (e.g., Sabatier principle and the d-band theory), thus allowing us to distinguish different catalysts intrinsically and design catalysts specifically. This thesis aims at providing a comprehensive investigation of the role of adsorption energy in electrocatalysis and the design strategies for the oxygen electrocatalyst in industrial applications of water splitting, hydrogen fuel cell, and hydrogen peroxide synthesis.